Accounting 2 - Hussain, Husnamaria; Mazali, Manizah; Nik Ibrahim, Nik Haslina; Abdul Rahman, Noredah; Mohd. Daud, Norhazni; Mohd. Noor, Rohana (IIUM Printing Sdn. Bhd., 2012)
Workbook for Accounting 2 students of Department of Quantitative Studies, Centre for Foundation Studies, IIUM